Proton Magnetic Resonance Spectroscopy Lactate/N-Acetylaspartate Within 48 h Predicts Cell Death Following Varied Neuroprotective Interventions in a Piglet Model of Hypoxia–Ischemia With and Without Inflammation-Sensitization - Pang, Raymand; Martinello, Kathryn A.; Meehan, Christopher; Avdic-Belltheus, Adnan; Lingam, Ingran; Sokolska, Magda; Mutshiya, Tatenda; Bainbridge, Alan; Golay, Xavier; Robertson, Nicola J. (Frontiers in Neurology, 2020)
Despite therapeutic hypothermia, survivors of neonatal encephalopathy have high rates of adverse outcome. Early surrogate outcome measures are needed to speed up the translation of neuroprotection trials. Thalamic lactate (Lac)/N-acetylaspartate (NAA) peak area ratio acquired with proton (1H) magnetic resonance spectroscopy (MRS) accurately predicts 2-year neurodevelopmental outcome. We assessed the relationship between MR biomarkers acquired at 24–48 h following injury with cell death and neuroinflammation in a piglet model following various neuroprotective interventions. Sixty-seven piglets with hypoxia–ischemia, hypoxia alone, or lipopolysaccharide (LPS) sensitization were included, and neuroprotective interventions were therapeutic hypothermia, melatonin, and magnesium. MRS and diffusion-weighted imaging (DWI) were acquired at 24 and 48 h. At 48 h, experiments were terminated, and immunohistochemistry was assessed. There was a correlation between Lac/NAA and overall cell death [terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)] [mean Lac/NAA basal ganglia and thalamus (BGT) voxel r = 0.722, white matter (WM) voxel r = 0.784, p < 0.01] and microglial activation [ionized calcium-binding adapter molecule 1 (Iba1)] (BGT r = −0.786, WM r = −0.632, p < 0.01). Correlation with marker of caspase-dependent apoptosis [cleaved caspase 3 (CC3)] was lower (BGT r = −0.636, WM r = −0.495, p < 0.01). Relation between DWI and TUNEL was less robust (mean diffusivity BGT r = −0.615, fractional anisotropy BGT r = 0.523). Overall, Lac/NAA correlated best with cell death and microglial activation. These data align with clinical studies demonstrating Lac/NAA superiority as an outcome predictor in neonatal encephalopathy (NE) and support its use in preclinical and clinical neuroprotection studies.